2018
DOI: 10.1016/j.jneb.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Perceptions and Preferences for 5 School Breakfast Program Models

Abstract: Teachers prefer traditional SBP model over BIC and other nontraditional models. Increased awareness and education regarding benefits and challenges of SBP models may increase teacher preference for nontraditional SBP models, especially BIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…To evaluate the success of BIC, several studies look to various stakeholders' perceptions of and attitudes toward the programs' impacts. Perception and attitude are important to measure because, as one study notes, stakeholder engagement is critical for the success of newly implemented SBPs 10,12,13 . Teachers may be especially critical stakeholders in implementing an effective breakfast program since they are often involved in supervising the delivery, consumption, and clean‐up of the food in the BIC model.…”
Section: Teacher Resistancementioning
confidence: 99%
“…To evaluate the success of BIC, several studies look to various stakeholders' perceptions of and attitudes toward the programs' impacts. Perception and attitude are important to measure because, as one study notes, stakeholder engagement is critical for the success of newly implemented SBPs 10,12,13 . Teachers may be especially critical stakeholders in implementing an effective breakfast program since they are often involved in supervising the delivery, consumption, and clean‐up of the food in the BIC model.…”
Section: Teacher Resistancementioning
confidence: 99%
“…Due to changes in school policies, sufficient evidence is now emerging that BIC is related to improved student attendance and academic learning 28 . These findings notwithstanding, there are school personnel, including teachers, who have argued that serving BIC interferes with student learning 29 . We did not find this to be the case.…”
Section: Implications For School Healthmentioning
confidence: 58%
“…However, generally, teachers prefer traditional breakfasts at home compared with those provided in schools and consider there may be a potential for waste in such in-school programs. 12 In this study found that several suggestions for the cafeteria program emerged, such as students want the program for lunch because some students did not have the habit of eating breakfast at home. School food contributes significantly to healthy eating behavior because it can form healthy eating habits and increase preference for new and diverse foods.…”
Section: Discussionmentioning
confidence: 87%
“…The most effective step of health promotion is through habitualizing healthy behaviors that are acquired early in a person's life, namely at the school age, whether elementary, junior high, or high school. 12 Unfortunately, in the Kulon Progo Regency there are still no CVD prevention school programs nor healthy diet and lifestyle promotion programs that target school-age children even though these ages are the ideal time to form healthy habits and behaviors.…”
Section: Development Of School Canteen and School Gardens Guidelines mentioning
confidence: 99%